S89 Bimodal iron oxide nanoparticles for hyperthermia therapy and MR imaging in cancer. (16th November 2010) - Parcell, K L; Kalber, T L; Walker-Samuel, S; Southern, P; Pankhurst, Q A; Lythgoe, M F; Janes, S M
Abstract : Introduction: Super paramagnetic iron oxide nanoparticles (SPION) offer attractive possibilities in biomedicine. Hyperthermia treatment of cancer involves introducing SPION into tumours and applying an alternating magnetic field (AMF). The AMF causes the SPION to heat, resulting in cell death. It has been shown previously that mesenchymal stem cells (MSCs) can be labelled with SPION, with no effect on cell survival, and that they will migrate to and integrate into lung metastases in vivo, following systemic administration. Furthermore, SPION can be used to follow the fate of labelled cells in the body as they cause a marked shortening in T2* on MRI. Therefore, MSCs labelled with SPION offer a promising delivery mechanism for treating lung metastases with hyperthermia therapy. In this preliminary study, the distribution of SPION labelled MSCs and the anti-tumour effect of hyperthermia treatment was evaluated in vitro and in a subcutaneous murine tumour model. Methods: MSCs were obtained from Tulane University, New Orleans. Cells were incubated overnight in 0.5 mg/ml of the SPION Ferucarbotranfor labelling. Subcutaneous tumours were induced by co-injecting 5 million OVCAR cells and 0.5 million SPION-labelled MSCs. Images of cells within mice were obtained on a 9.4Thorizontal bore Varian NMR system. A 10 mT 1.05 MHz AMF was generated using a copper solenoid coil, diameter 3 cm. Mice were placed inside the coil under anaesthesia and each hyperthermia session lasted 20 min. Post-heating histology was obtained. Results: Hyperthermia treatment caused a rise in temperature up to 60°C in vitro and a rise in tumour temperature of up to 4°C above body temperature in vivo (Abstract S89 Figure 1 ), detected by thermal imaging and with fibre optic probes. Iron was confirmed in the tumour using MR imaging and histology. Discussion: This study demonstrates the potential of SPION to act as an imaging agent and cancer therapy. SPION-labelled MSCs can be imaged in vivo in very low cell numbers. We have demonstrated that the application of an alternating magnetic field causes a temperature rise in these cells, both in vitro and in vivo . In the future, we will optimise SPION as an imaging and hyperthermia agent, for the targeted treatment of lung metastases.